Oxygen Saturation and Suck-Swallow-Breathe Coordination of Term Infants during Breastfeeding and Feeding from a Teat Releasing Milk Only with Vacuum - Vanessa S. Sakalidis; Holly L. McClellan; Anna R. Hepworth; Jacqueline C. Kent; Ching Tat Lai; Peter E. Hartmann; Donna T. Geddes (Hindawi Limited, 2012)
Background. Vacuum is an important factor in milk removal from the breast, yet compression is the predominant component of milk removal from bottle teats. Since bottle-feeding infants have lower oxygen saturation, vacuum levels, and different suck-swallow-breathe (SSwB) coordination to breastfeeding infants, we hypothesised that when infants fed from a teat that required a vacuum threshold of −29 mmHg for milk removal, that oxygen saturation, heart rate, and suck-swallow-breathe (SSwB) patterns would be similar to those of breastfeeding. Study Design. Infants (𝑛=16) were monitored during one breastfeed and one feed from the experimental teat. Simultaneous recordings were made of oxygen saturation, heart rate, vacuum, tongue movement, respiration, and swallowing. Results. There were no differences in oxygen saturation and heart rate between the breast and the teat. Infants displayed fewer sucks and breaths per swallow during nutritive sucking (NS) compared to non-nutritive sucking (NNS). The number of sucks per breath was similar for NS and NNS although respiratory rates were slower during NS. These patterns did not differ between the breast and the teat. Conclusion. These results suggest that vacuum may be conducive to safe and coordinated milk removal by the infant during both breast and bottle-feeding.